2012
DOI: 10.1177/0310057x1204000214
|View full text |Cite
|
Sign up to set email alerts
|

Ketofol (Mixture of Ketamine and Propofol) Administration in Electroconvulsive Therapy

Abstract: Electroconvulsive therapy (ECT) is a common treatment method used in severe depression and other psychiatric diseases. Currently, most ECT procedures are carried out with muscle paralysis under general anaesthesia. The anticonvulsant properties of sedative and hypnotic drugs used during general anaesthesia may reduce the efficacy of ECT. It is important to establish an accurate balance between adequate anaesthesia depth and optimal seizure duration. Moreover, the electrical current applied during the ECT stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…Incidence of hallucination and nausea were lower, although were not statistically signifi cant. Kayhan et al [27], evaluated the effect of a ketaminepropofol combination (ketofol) for electroconvulsive therapy (ECT) on seizure activity, hemodynamic response and recovery parameters compared to propofol alone. The seizure durations in both groups were similar.…”
Section: Discussionmentioning
confidence: 99%
“…Incidence of hallucination and nausea were lower, although were not statistically signifi cant. Kayhan et al [27], evaluated the effect of a ketaminepropofol combination (ketofol) for electroconvulsive therapy (ECT) on seizure activity, hemodynamic response and recovery parameters compared to propofol alone. The seizure durations in both groups were similar.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the hemodynamic parameters were stable in the ketofol group. 20 Hashemi et al studied two different concentrations of ketofol in children and reported that recovery time and adverse events were reduced in low ketamine concentration group. 21 Phillips et al studied propofol monotherapy versus ketofol in PSA and concluded that sedation with ketofol was adequate but propofol alone need deep sedation level.…”
Section: Discussionmentioning
confidence: 99%
“…Οι Aisworth et al το 2019 συμπεριέλαβαν 18 διπλά τυφλές τυχαιοποιημένες ελεγχόμενες μελέτες από τις οποίες δεν διαπιστώθηκε διαφορά στη βαρύτητα των συμπτωμάτων στο τέλος των συνεδριών ΗΣΘ μεταξύ των ασθενών που έλαβαν κεταμίνη ως αναισθητικό (μόνη ή σε συνδυασμό) και της ομάδας ελέγχου. 25,[27][28][29][30][31][33][34][35][36]38,42,43,[45][46][47][48] Επιπλέον, δεν διαπιστώθηκε ταχύτερη απάντηση στην ΗΣΘ με κεταμίνη σε σχέση με την ΗΣΘ με άλλο αναισθητικό.…”
Section: η κεταμίνη ως αναισθητικό στην ηλεκτροσπασμοθεραπείαunclassified